How Smart Are You at Traveling? Adoption of Smart Tourism Technology in Influencing Visiting Tourism Destinations - KUSDIBYO, Lusianus; RAFDINAL, Wahyu; SUSANTO, Eko; SUPRINA, Rina; NENDI, Ikhsan; ABDUROKHIM, Abdurokhim (Journal of Environmental Management and Tourism; Vol 14 No 4 (2023): JEMT, Volume XIV, Issue 4(68), Summer 2023DO - 10.14505/jemt.14.4(68).13, 2023)
This study analyses smart tourism technology adoption's role in influencing visiting destinations by providing unity to the technology acceptance model (TAM) mechanism and the model theory of planned behaviour (TPB), using 324 samples of tourists from Indonesia. This study uncovers eight dimensions of innovative tourism technology by applying exploratory factor analysis. A variance-based structural equation model is used to evaluate the model and test hypotheses. This study reveals that the integrated TAM and TPB model can better explain smart tourism technology adoption and visiting tourism destinations. The integrated model is suitable for adopting smart tourism technology, which is the basis for tourist behaviour in tourist destinations. From its finding, this study offers a foundation for formulating an implementation strategy for using appropriate smart tourism technology to attract tourists. By originality, this study describes empirical evidence to promote the values of the smart tourism technology dimensions in enhancing tourist intention to use smart tourism technology and visit tourism destinations.